Aplikasi Mikroenkapsulat Minyak Sawit Merah pada Mi Instan - Nur Wulandari; Stephanie Angka; Dede Robiatul Adawiyah; Nurheni Sri Palupi (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2015)
Indonesia suffered from several nutrition problems, one of them is vitamin A deficiency. On the other hand, people are concerned about the excess level of syntetic food colorant consumption. Red palm oil (RPO) is one of the solutions of the problem, because its high carotene content can act as pro- vitamin A and yellowish food colorant. Microencapsulation of RPO is one way to protect carotene content during process. The aim of this research is to obtain informations about application of micro-encapsulated RPO (MRPO) in instant noodle. Wall materials used for RPO microencapsulation were maltodextrin and sodium caseinate. MRPO had 1.15% moisture content, 123.42 μg carotene/g powder, and 91.96% water solubility. MRPO then applied in instant noodle as much as 6.5% and 13% of wheat our to ful ll 20% (120 RE/person/day) of Nutrients Labelling Value (NLV) for adults (Kemenkes 2013). Instant noodle with 6.5% MRPO contained 127.89 RE. It also had 10.53% solid loss during cooking and 146.99% elongation. Addition of 6.5% MRPO in instant noodle had similar aroma and taste with commercial one, though it had softer texture and more yellowish color. MRPO process succeeded to keep 61.89 – 79.53% of carotene content during the microencapsulation and noodle making process.